Efektivitas Metode Tamyiz terhadap Memori dalam Mempelajari Alquran pada Santri Pondok Pesantren Quran - Alfi Fauziyyah; Ulfiah Ulfiah; Ila Nurlaila Hidayat (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2018)
One way to memorize and understand the Qur'an is to learn Arabic. Learning Arabic is still considered a difficult thing for most people. Also, students who studied the Qur'an are only able to read and memorize the verses of the Qur'an without understand the meaning of these verses. This study aims to determine the effect of Tamyiz Method on memory in learning Qur'an. This research used true-experimental method with before match after design. The subjects were students of Islamic boarding school of Qur'an Al-Lathifah, each consisting of 35 people in the experimental group and the control group. The result shows that Tamyiz Method influences memory in learning Qur'an. This method has repetition process, that is elaborative rehearsal and there is mnemonic learning strategy. Qur’an is memorized using imagination and word made using popular songs, making it easier for students in saving information in long-term memory.